Improving Maternity Care by Eliminating Racism and Inequities. Issue 2 (March 2021) - Killion, Molly M.
Abstract : Maternity care in the United States is not equitable for all women. Black and Indigenous People of Color have poorer maternal and neonatal outcomes when compared to white women. Our maternity nursing expert, Molly Killion, discussed several recent publications on maternity care inequities and racism and how the health care system can be improved so that all women and babies have the same opportunities for good health.